Multi-channel silk sponge mimicking bone marrow vascular niche for platelet production. (September 2018) - Tozzi, Lorenzo; Laurent, Pierre-Alexandre; Di Buduo, Christian A.; Mu, Xuan; Massaro, Angelo; Bretherton, Ross; Stoppel, Whitney; Kaplan, David L.; Balduini, Alessandra
Abstract: In the bone marrow, the interaction of progenitor cells with the vasculature is fundamental for the release of blood cells into circulation. Silk fibroin, derived from Bombyx mori silkworm cocoons, is a promising protein biomaterial for bone marrow tissue engineering, because of its tunable architecture and mechanical properties, the capacity to incorporate labile compounds without loss of bioactivity and the demonstrated ability to support blood cell formation without premature activation. In this study, we fabricated a custom perfusion chamber to contain a multi-channel lyophilized silk sponge mimicking the vascular network in the bone marrow niche. The perfusion system consisted in an inlet and an outlet and 2 splitters that allowed funneling flow in each single channel of the silk sponge. Computational Fluid Dynamic analysis demonstrated that this design permitted confined flow inside the vascular channels. The silk channeled sponge supported efficient platelet release from megakaryocytes (Mks). After seeding, the Mks localized along SDF-1α functionalized vascular channels in the sponge. Perfusion of the channels allowed the recovery of functional platelets as demonstrated by increased PAC-1 binding upon thrombin stimulation. Further, increasing the number of channels in the silk sponge resulted in a proportional increase in the numbers of platelets recovered, suggesting applicability to scale-up for platelet production. In conclusion, we have developed a scalable system consisting of a multi-channeled silk sponge incorporated in a perfusion chamber that can provide useful technology for functional platelet production ex vivo .